Characteristics of intussusception in the period of arbitrary Rotavirus vaccination. Issue 1 (2nd November 2022) - Nakamura, Mutsumi; Yoshimaru, Koichiro; Matsuura, Toshiharu; Hamada, Hiroshi; Motomura, Yoshitomo; Hayashida, Makoto; Ohga, Shouichi; Tajiri, Tatsuro; Hara, Toshiro; Taguchi, Tomoaki
Abstract: Background: In November 2011, rotavirus (RV) vaccine was launched in Japan as a voluntary vaccination to prevent RV‐associated gastroenterocolitis. We examined the characteristics of intussusception following RV vaccination in our two centers. Methods: We investigated intussusception patients <16 years old from January 2006 to September 2020. Patients were categorized according to the period (before [Group A] or after the introduction of arbitrary RV vaccination [Group B]). The patient characteristics and treatment of intussusception were retrospectively investigated. Results: During the study period, 560 patients (group A, n = 233; group B, n = 327) were identified. The distribution of patients who were 0–6 months old was not significantly different between the groups (group A, n = 12, 5.2%; group B, n = 18, 5.5%). Among these 18 patients in Group B, 7 were vaccinated against RV, and 10 were not. One patient was excluded due to incomplete data. On comparing patients with and without RV vaccination, the mean age at the onset of intussusception was 3.3 ± 0.4 versus 4.0 ± 0.3 months ( P = 0.19), the mean interval from the onset to treatment was 7.5 ± 2.4 versus 16.0 ± 2.2 h ( P = 0.03), the time of the contrast enema for treatment was 9.1 ± 3.3 versus 7.7 ± 2.8 min ( P = 0.76), and the final pressure of the contrast enema was 92.5 ± 4.4 versus 92.2 ± 4.4 cmH2 O ( P = 0.97). Conclusions: Arbitrary RV vaccination did not influence the age distribution of intussusception, and the interval from the onset to treatment was significantly shorter in the patients with RV vaccination than in those without it. Recognizing the presence of intussusception following RV vaccination enables accurate treatment.